Coalescent-based species delimitation in the sand lizards of the Liolaemus wiegmannii complex (Squamata: Liolaemidae) - Villamil, Joaquín (2019)
Coalescent-based algorithms coupled with the access to genome-wide data have become powerful tools forassessing questions on recent or rapid diversification, as well as delineating species boundaries in the absence of reciprocal monophyly. In southern South America, the diversification of Liolaemus lizards during the Pleistocene is well documented and has been attributed to the climatic changes that characterized this recent period of time. Past climatic changes had harsh effects at extreme latitudes, including Patagonia, but habitat changes at intermediate latitudes of South America have also been recorded, including expansion of sand fields over northern Patagonia and Pampas). In this work, we apply a coalescent-based approach to study the diversification of the Liolaemus wiegmannii species complex, a morphologically conservative clade that inhabits sandy soils across northwest and south-central Argentina, and the south shores of Uruguay. Using four standard sequence markers (mitochondrial DNA and three nuclear loci) along with ddRADseq data we inferred species limits and a time calibrated species tree for the L. wiegmannii complex in order to evaluate the influence of Quaternary sand expansion/retraction cycles on diversification. We also evaluated the evolutionary independence of the recently described L. gardeli and inferred its phylogenetic position relative to L. wiegmannii. We find strong evidence for six allopatric candidate species within L. wiegmannii, which diversified during the Pleistocene. The Great Patagonian Glaciation (∼1 million years before present) likely split the species complex into two main groups: one composed of lineages associated with sub-Andean sedimentary formations, and the other mostly related to sand fields in the Pampas and northern Patagonia. We hypothesize that early speciation within L. wiegmannii was influenced by the expansion of sand dunes throughout central Argentina and Pampas. Finally, L. gardeli is supported as a distinct lineage nested within the L. wiegmannii complex.